2020
DOI: 10.3390/universe6100177
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Effects in Orbital Motion of the S-Stars at the Galactic Center

Abstract: The Galactic Center star cluster, known as S-stars, is a perfect source of relativistic phenomena observations. The stars are located in the strong field of relativistic compact object Sgr A* and are moving with very high velocities at pericenters of their orbits. In this work we consider motion of several S-stars by using the Parameterized Post-Newtonian (PPN) formalism of General Relativity (GR) and Post-Newtonian (PN) equations of motion of the Feynman’s quantum-field gravity theory, where the positive ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Lense-Thirring Precession of the S2 Star Due to Spin of Sgr A* For the very precise calculations the Lense-Thirring (LT) precession caused by the SMBH spin should be also taken into account in the overall pN precession. In the case of the recently discovered ultra-eccentric S-stars S4711, S62, S4714 [101][102][103][104], the LT precession was studied in [102] and it was found that it is much smaller than Schwarzschild precession. Namely, the ratio between the LT precession for a rotating SMBH with dimensionless spin χ g = 0.5 and the Schwarzschild precession for these stars is around 2.7, 2.3 and 0.86%, respectively [102].…”
Section: Resultsmentioning
confidence: 99%
“…Lense-Thirring Precession of the S2 Star Due to Spin of Sgr A* For the very precise calculations the Lense-Thirring (LT) precession caused by the SMBH spin should be also taken into account in the overall pN precession. In the case of the recently discovered ultra-eccentric S-stars S4711, S62, S4714 [101][102][103][104], the LT precession was studied in [102] and it was found that it is much smaller than Schwarzschild precession. Namely, the ratio between the LT precession for a rotating SMBH with dimensionless spin χ g = 0.5 and the Schwarzschild precession for these stars is around 2.7, 2.3 and 0.86%, respectively [102].…”
Section: Resultsmentioning
confidence: 99%
“…For the very precise calculations the Lense-Thirring (LT) precession caused by the SMBH spin should be also taken into account in the overall pN precession. In the case of the recently discovered ultra-eccentric S-stars S4711, S62, S4714 [101][102][103][104], the LT precession was studied in [102] and it was found that it is much smaller than Schwarzschild precession. Namely, the ratio between the LT precession for a rotating SMBH with dimensionless spin χ g = 0.5 and the Schwarzschild precession for these stars is around 2.7, 2.3 and 0.86%, respectively [102].…”
Section: Resultsmentioning
confidence: 99%
“…Besides Schwarzschild precession, relativistic frame-dragging due to the spin of SMBH, also known as the Lense-Thirring (LT) effect, could cause orbital precession. The LT precession in the case of several S-stars was studied in references [18,[64][65][66][67], and it was found that it is much smaller than Schwarzschild precession [18,65]. The spin of Sgr A * was estimated to χ g < 0.1 by the observed distribution of the orbital planes of the S-stars [68].…”
Section: Gravitational Potentials and The Stellar Dynamicsmentioning
confidence: 99%